The Implementation Of Administrative Bureaucracy Reform At Bengkulu Regional Office Of The Ministry Of Law And Human Rights Based On Presidential Regulation Number 81 Of 2010 Concerning The Grand Design Of Bureaucracy Reform Of 2010-2025 - Afrilinda Afrilinda; Edra Satmaidi; Iskandar Iskandar (Universitas Bengkulu, 2022)
The purpose of this study is to analyze and to describe the implementation of administrative bureaucratic reform at Bengkulu regional office of Ministry of Law and Human Rights of Bengkulu based on Presidential Regulation Number 81 of 2010 concerning the Grand Design of Bureaucratic Reform of 2010-2025, and to analyze the obstacles in the implementation of administrative bureaucratic reform at Bengkulu regional office of Ministry of Law and Human Rights. This research was a normative legal research. The analysis of legal materials was carried out in a qualitative juridical manner. The results of the study show that: Firstly, the implementation of administrative bureaucratic reform at the Bengkulu Regional Office of the Ministry of Law and Human Rights has been carried out for the needs of Bureaucratic Reform. Secondly, there are obstacles in the implementation of administrative bureaucratic reform at the Bengkulu Regional Office of the Ministry of Law and Human Rights, namely: The juridical obstacles consist of the absence of technical legislation for performance improvement and the absence of Standard Operating Procedures (SOPs) that can build a common perception, commitment, involvement in program implementation and bureaucratic reform activities at all levels of employees. Technical obstacles, namely the limited quantity and quality of Human Resources (HR) and facilities and infrastructure. By establishing an organizational structure based on the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 30 of 2018 concerning the Organization and Work Procedure of the Regional Office of the Ministry of Law and Human Rights, it can be a solution to achieve efficiency and effectiveness in the implementation of the tasks of the government bureaucratic apparatus.